PENGARUH KOMPENSASI TERHADAP KEPUASAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI PADA KARYAWAN KONTRAK PADA PT BANK NEGARA INDONESIA, TBK KANTOR CABANG PONTIANAK - B31111183, Anggoro Febrianto (Jurnal Manajemen Update, 2016)
PT. BNI (Persero), Tbk Branch Pontianak is one branch of PT Bank Negara Indonesia Tbk. In carrying out its activities can not be separated from the problems of the human resources involved in the institution. In the human resources aspects of PT. BNI (Persero), Tbk Branch Pontianak has been implementing various compensation policies in order to enhance work motivation and employee satisfaction contract. The purpose of this study was to determine the effect on employee motivation compensation contracts at               PT. Bank Negara Indonesia Tbk Branch Office of Pontianak and to determine the effect of work motivation on employee job satisfaction as well as the contract to determine the effect of compensation on employee job satisfaction contracts on PT. Bank Negara Indonesia Tbk Branch Office of Pontianak. This research method is associative. Data collection techniques: interviews, questionnaires and documentary studies. The population in this study were all contract employees numbering 117 people in 2015. So samples taken is a contract employee at PT. Bank Negara Indonesia Tbk Branch Office in the city of Pontianak Pontianak totaling 98 people, while the method used for sampling with purposive sampling technique and analyzed quantitatively. Results of the study as follows: There is a significant influence on employee motivation compensation contracts at PT. Bank Negara Indonesia Tbk Branch Office of Pontianak and no significant effect of work motivation on employee job satisfaction contract in PT. Bank Negara Indonesia Tbk Branch Office of Pontianak and no significant effect on job satisfaction employee compensation contracts at PT. Bank Negara Indonesia Tbk Branch Office of Pontianak.     Keywords: Compensation, Work Motivation, Job Satisfaction